2017
DOI: 10.1039/c7py00831g
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linkable multi-stimuli responsive hydrogel inks for direct-write 3D printing

Abstract: Triple-stimuli responsive hydrogel can be 3D printed and cross-linked in the presence of a photoradical generator and 365 nm UV light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…From am olecular design perspective, intensively investigated block copolymer phase segregation [68,69,[126][127][128] is ap romis-ing path to design DIW polymers. Furthermore, the rich toolbox containing av ariety of supramolecular binding motifs could also be transferred for the development of DIW inks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From am olecular design perspective, intensively investigated block copolymer phase segregation [68,69,[126][127][128] is ap romis-ing path to design DIW polymers. Furthermore, the rich toolbox containing av ariety of supramolecular binding motifs could also be transferred for the development of DIW inks.…”
Section: Discussionmentioning
confidence: 99%
“…To invert the hydrophobic and hydrophilic segments of the amphiphilic polymer, Nelson et al. reported a series of triblock copolymers (P i PrGE‐ b ‐PEG‐ b ‐P i PrGE) composed of a polyethylene glycol (PEG) core and two poly(isopropyl glycidyl ether) (P i PrGE) tails (Figure a) . These copolymers aggregate in aqueous solutions to form micelles.…”
Section: Facilitating 3d Printability To Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that such physical hydrogels are very suitable for DIW applications, which were indeed demonstrated as capable of printing free‐standing patterned structures with good fidelity. The authors suggested that the gel yield stress is also an important parameter to be considered for gel extrusion, [ 83 ] as it provides an indirect indication of the gel's ability to support subsequent stacked layers during 3D printing. Nelson and co‐workers have also demonstrated that both dynamic and the static yield stress could be tuned by varying hydrogel formulations and are critical rheological parameters for printability.…”
Section: Materials Designs For 3d Printabilitymentioning
confidence: 99%
“…The use of dynamic bonds which undergo reversible breaking, exchange and reformation could be utilized to modify the printability of polymers as well as imparting various advanced functions. [ 41–58,62–67,59,68,60,69,70,72,61,73,71,82,86–88,74–81,83–85,89–133,244,258 , …”
Section: Summary and Perspectivementioning
confidence: 99%